Image Hiding Using Variable Length Least Significant Bits Embedding - Jasim, Abbas A. (Iraqi Journal for Electrical and Electronic Engineering, 2014)
In this work a new hiding system is proposed. It is based on Least Significant Bits (LSB) embedding of secrete image into another cover image. The proposed hiding algorithm embeds the secrete image bits in the least significant bits of the cover image pixels such that the number of secrete image bits that are embedded in least significant bits of cover image pixel is variable and determined randomly. Such cover image pixel may contain no secrete information bit, one bit, two bits , or three bits according to the pseudo random number generator that generates integer numbers randomly between 0 and 3. The resulting image (the cover image within which the secret image is hidden) is called stego_image. Stego_image is closely related to the cover image and does not show any details of the secret information. It ensures that the eavedroppers will not have any suspicion that message bits are hidden in the image. The proposed system achieves perfect reconstruction of the secret message.